2014
DOI: 10.32738/jeppm.201407.0004
|View full text |Cite
|
Sign up to set email alerts
|

 Risk Management Capability Maturity and Performance of Complex Product and System (CoPS) Projects with an Asian Perspective

Abstract: Complex Products and Systems (CoPS) are high value, technology and engineering-intensive capital goods. The motivation of this study is the persistent high failure rate of CoPS projects, Asian CoPS provider's weak capability and lack of specific research on CoPS risk management. This paper evaluates risk management maturity level of CoPS projects against a general CoPS risk management capability maturity model (RM-CMM) developed by the authors. An Asian based survey was conducted to investigate the value of RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Risk taking largely reflects the organization's willingness to break away from the tried-and-true venture into the unknown (Chua, 2014; Perez-Luno et al, 2011). The management of risks is a growing area of concern (Ren et al, 2014) which can lead to a range of benefits for both projects and organisations. In case on innovative projects, it provides guidance for decision making about alternative options, increases confidence in the project success and reduces the risk of unexpected events that can cause delays and excess expenditure (Porananond and Thawesaengskulthai, 2014).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…Risk taking largely reflects the organization's willingness to break away from the tried-and-true venture into the unknown (Chua, 2014; Perez-Luno et al, 2011). The management of risks is a growing area of concern (Ren et al, 2014) which can lead to a range of benefits for both projects and organisations. In case on innovative projects, it provides guidance for decision making about alternative options, increases confidence in the project success and reduces the risk of unexpected events that can cause delays and excess expenditure (Porananond and Thawesaengskulthai, 2014).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…A similar finding was reported in another multiple-case study by Albrecht and Spang 10 which suggested “complexity” as a moderation variable. A quantitative study was carried out by Ren et al 49 for complex product and system projects within Singapore and Chinese settings and found a positive, moderated relationship between PRMM and project performance. The moderation variable was “complexity and uncertainty” at the project level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors have investigated about risk and risk management, raising the interest from different industries and organizations Aven, 2010;Hillson, 2007;Ward and Chapman, 2003;Aven, 2016). The risk management process includes five main stages (Baloi and Price, 2003;Hillson, 2007;Ward and Chapman, 2003;Banaitienė et al, 2011;Carter and Chinyio, 2010;Dikmen et al, 2008;ISO, 2009;NASA, 2011;Osipova and Eriksson, 2013;Papadaki et al, 2010;Ren et al, 2014;Standards Australia, 2007). These stages are as follows: 1) risk management planning; 2) risk identification; 3) risk analysis and evaluation; 4) response plan to risks; and 5) monitoring and control of risks.…”
Section: Risk Managementmentioning
confidence: 99%